INFLUENCE TRANSFORMATIONAL LEADERSHIP OF ORGANIZATIONAL CULTURE AND TOTAL QUALITY MANAGEMENT AND MOTIVATION OF WORK AND ORGANIZATIONAL PERFORMANCE FACULTY OF ENGINEERING IN PRIVATE VOCATIONAL SCHOOL KALIMANTAN AREA - et.al, Lukman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study uses survey techniques by distributing questionnaires, then the Data or Obtained information is processed by statistical methods using WarpPLS software. The purpose of data analysis uses PLS (Partial Least Square). This research is explanatory research that aims to test a theory or hypothesis to Strengthen or reject a pre-existing theory or research hypothesis. All private colleges of the Faculty of Engineering in Kalimantan, are the population in this study. Data collection techniques using a questionnaire with a Likert scale, and the data analysis techniques using the Structural Equation Model-Partial Least Square (SEM-PLS) approach to determine the effect of indicators with the construct and the variance of the results of the dependent variable. The Results Showed that: Transformational Leadership has a significant positive impact on work motivation, as well as the results of the relationship of transformational Leadership on organizational performance, have a significant positive effect. Work motivation is influenced positively and significantly by company culture, and organizational culture had a significant positive impact on organizational performance; total quality management had a significant negative effect. On work motivation, overall quality management has a significant positive effect on organizational performance. The relationship of work motivation to organizational performance has a positive and significant effect. The corporate culture had a significant positive effect on organizational performance; total quality management had a significant negative effect. On work motivation, total quality management has a significant positive impact on organizational performance. Work motivation has a significant positive effect on the organizational performance of the Faculty of Engineering Private University in Borneo. The corporate culture had a significant positive effect on organizational performance. Total quality management had a significant negative effect. On work motivation, total quality management has a significant positive effect on organizational performance.